Analysis of the Empowerment Level of Smoked Fish Processors Tandipang (Dussumieria acuta) - Sondakh, Srie J.; Suhaeni, Siti; Rantung, Steelma (Jurnal Ilmiah Platax, 2025)
The method used in this study is the case study method. Data were collected from two sources, namely primary data and secondary data. The population in this study consists of smoked Tandipang fish processors in Tumpaan Subdistrict. Data collection was done using the census method, where the entire population was selected as respondents, with 14 smoked Tandipang fish processors chosen as the sample. The data collected include primary and secondary data. Primary data was gathered through observations and interviews guided by a questionnaire, while the data obtained were analyzed using both quantitative and qualitative descriptive analysis. Family welfare was measured based on objective and subjective welfare. The analysis concluded that the average annual income of smoked Tandipang fish processors in Tumpaan Subdistrict is IDR 88,168,000, earned from working as fish processors and side jobs. The fishermen’s family expenditures consist of food and non-food expenses, with 85.68% of their total income spent solely on food. The empowerment level of traditional fishermen in Belang Subdistrict is still considered low from both economic and non-economic aspects. Economically, more than 50% of fishermen’s income is used to meet food needs only. From all non-economic aspects, the community of smoked Tandipang fish processors in the Tumpaan Subdistrict is also still categorized as lacking empowerment. Keywords: Hygienic, industry, sanitation, fiber. Abstrak Metode yang dipakai dalam penelitian ini adalah metode studi kasus. Data yang dikumpulkan melalui dua sumber yaitu data primer dan data sekunder. Populasi dalam penelitian ini adalah pengolah ikan Tandipang asap yang ada di Kecamatan Tumpaan. Teknik pengambilan data dilakukan dengan metode sensus, yaitu seluruh populasi akan diambil sebagai responden dan dipilih sebanyak 14 responden pengolah ikan tandipang asap. Data yang dikumpulkan berupa data primer dan data sekunder. Teknik pengumpulan data primer dengan observasi dan wawancara yang dipandu dengan kuesioner, sedangkan data yang diperoleh dianalisis dengan menggunakan analisis deskriptif kuantitatif dan deskriptif kualitatif. Kesejahteraan keluarga diukur berdasarkan kesejahteraan objektif dan kesejahteraan subjektif. Berdasarkan hasil analisis, disimpulkan bahwa rata-rata pendapatan keluarga pengolah ikan Tandipang asap yang ada di Kecamatan Tumpaan per tahun adalah Rp.88.168.000 yang diperoleh dari bekerja sebagai pengolah ikan dan pekerjaan sampingan. Pengeluaran keluarga nelayan terdiri dari pengeluaran untuk pangan dan non pangan, 85,68% dari total pendapatan nelayan hanya untuk memenuhi kebutuhan makanan saja. Tingkat keberdayaan nelayan tradisional di Kecamatan Belang masih termasuk rendah dilihat dari aspek ekonomi maupun non ekonomi. Secara ekonomi karena sebagian besar atau lebih dari 50% pendapatan nelayan hanya digunakan untuk memenuhi kebutuhan pangan saja. Dilihat dari semua aspek non ekonomi masyarakat pengolah ikan Tandipang asap yang ada di Kecamatan Tumpaan juga masih dikategorikan kurang berdaya Kata kunci: Higienis, industri, sanitasi, serat.